Research on Extreme Signed Graphs with Minimal Energy in Tricyclic Signed Graphs S(n, n + 2) - Yajing Wang; Yubin Gao (Complexity)
A signed graph is acquired by attaching a sign to each edge of a simple graph, and the signed graphs have been widely used as significant computer models in the study of complex systems. The energy of a signed graph S can be described as the sum of the absolute values of its eigenvalues. In this paper, we characterize tricyclic signed graphs with minimal energy.